ĐK: \(x\ge1\)
Ta có: \(\sqrt{x^2+6x+9}=x-1\)
\(\Leftrightarrow x^2+6x+9=x^2-2x+1\)
\(\Leftrightarrow8x=-8\Leftrightarrow x=-1\left(loại\right)\)
⇒ ptvn
Điền vào dấu 3 chấm là số 0 nhé
\(\sqrt{x^2+6x+9}=x-1\)
<=> \(\sqrt{\left(x+3\right)^2}=x-1\)
<=> \(\left|x+3\right|=x-1\)
<=> \(\left[{}\begin{matrix}x+3=x-1\left(x\ge-3\right)\\x+3=-x+1\left(x< -3\right)\end{matrix}\right.\)
<=> \(\left[{}\begin{matrix}x-x=-1+3\\x+x=1-3\end{matrix}\right.\)
<=> \(\left[{}\begin{matrix}0=2\left(VLí\right)\\2x=-2\end{matrix}\right.\)
<=> 2x = -2
<=> x = -1
Vậy nghiệm của phương trình là \(S=\left\{-1\right\}\)